Mitochondrial redox system: A key target of antioxidant therapy to prevent acquired sensorineural hearing loss - Baek, Jeong-In; Kim, Ye-Ri; Lee, Kyu-Yup; Kim, Un-Kyung (Frontiers in Pharmacology, 2023)
Noise (noise-induced hearing loss), and ototoxic drugs (drug-induced ototoxicity), and aging (age-related hearing loss) are the major environmental factors that lead to acquired sensorineural hearing loss. So far, there have been numerous efforts to develop protective or therapeutic agents for acquired hearing loss by investigating the pathological mechanisms of each types of hearing loss, especially in cochlear hair cells and auditory nerves. Although there is still a lack of information on the underlying mechanisms of redox homeostasis and molecular redox networks in hair cells, an imbalance in mitochondrial reactive oxygen species (ROS) levels that enhance oxidative stress has been suggested as a key pathological factor eventually causing acquired sensorineural hearing loss. Thus, various types of antioxidants have been investigated for their abilities to support auditory cells in maintenance of the hearing function against ototoxic stimuli. In this review, we will discuss the scientific possibility of developing drugs that target particular key elements of the mitochondrial redox network in prevention or treatment of noise- and ototoxic drug-induced hearing loss.